Evolving Payment Platform for Developing Countries - Nana Mbinkeu, Rodrigue Carlos (International Journal of Interactive Mobile Technologies (iJIM), 2013)
This article shows the impact of the growing adoption of mobile phones in the field of money transfer in Africa but also their uses in the field of retail payments or micropayments that is financial transaction from person to person (P2P) for small amounts. We show how these innovations will continue to improve the quality of life of Africans especially those in rural areas. We present M-Pesa as a mobile payment system which has had great success in Kenya. We identify the fundamental principles of success thus this enabled us to create an ECOPAY platform which is an innovative mobile payment system. Our platform provides different types of m-payment like as B2C, B2B or P2P using the mobile phone or others devices. Each transaction is secure by using encrypted message and encrypted connection between the devices and the ECOPAY servers.